Analisis Hadis Dha'if dan Maudhū' dalam Tafsir Al-Khazin Serta Implikasinya Terhadap Penafsiran Al-Qur'an - Edi Hermanto; Fauzan Murtadho; Aqri Habibi; Raffa Arya; Sapar Hasibuan (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
Hadith holds an important position in the study of tafsir because it functions as an explanation of the verses of the Qur'an. However, the use of hadith in interpretation requires attention to the quality and validity of the narrations used, because the presence of da'if and maudhū' hadith can influence the understanding of the contents of the Qur'an. This study aims to analyze the existence of da'if and maudhū' hadith in Tafsir al-Khazin and explain their implications for the interpretation of the Qur'an. This study uses a qualitative method with a type of library research. The analysis was carried out by tracing the narrations used in Tafsir al-Khazin and assessing their quality based on the assessment of hadith scholars regarding sanad and matan. The results of the study show that Tafsir al-Khazin as one of the books of tafsir based on narrations contains hadith with varying quality, including narrations that are categorized as da'if and maudhū' based on the study of hadith science. The existence of these narrations does not necessarily diminish the scientific value of Tafsir al-Khazin, but rather demonstrates the characteristics of the classical exegetical tradition, which places greater emphasis on compiling various narrations to explain Quranic verses. Therefore, hadith criticism is an important aspect in tafsir studies to ensure that the use of narrations to support Quranic interpretation remains valid and scientifically justifiable.